A PENGARUH PENERAPAN METODE TANYA JAWAB MULTI ARAH TERHADAP HASIL BELAJAR SISWA MATERI PYTHAGORAS - Moh. Syukron Maftuh; Eko Sugandi (Program Studi Pendidikan Matematika STKIP PGRI Sidoarjo, 2023)
This research is motivated by the importance of overcoming the lack of understanding of student’s material to improve student learning outcomes, namely question and answer multi direction method. This learning method, students are expected to be more active, creative, and able to develop concepts to solve mathematical problems appropriately. The aim is to determine the effect of question and answer multi-direction on mathematic learning outcome in pythagorasin 8th class students of SMP N 19 Surabaya. The design used is a post-tes-only control group. The population in this research were all 8th students at SMP N 19 Surabaya. The sampling technique used is purposive sampling, the samples obtained are class VIII-E and class VIII-F. The data collection technique used is the test method. The data analysis technique used normality lest, homogenity, and t-test. Based on analysis of the data obtained that the sample is normally distributed and homogenous. Bu analyzing the data using the t-test, it was obtained that with a significant level of 0,05 and . This shows that is greater than . Then it was concluded that there was an effect of question and answer multi-direction on mathematic learning outcome in pythagoras in 8th class students of SMP N 19 Surabaya.